Indian women in the age of globalization: Problems & possibilities - Ojha, Pankaj Kumar (2013)
Highlights the problems faced by working Indian women during involvement in production procedure in the traditional ways.Describes the possibilities and opportunities available to them in an open economy.States the importance of information technology to cope with the problems of Indian working women and to enhance their happiness and prosperity. Globalization is the changes in societies and the word economy that result from dramatically increased international trade and cultural exchange.Globalization advocates the increase of trade and investing due to the falling of barriers and interdependence of countries in economic context, the term refers almost exclusively to the effects of trade, particularly trade liberalization or free trade. Although globalization and economic liberalization have become the factor which determine the direction of our lives. There is little consensus on how to approach the subject of globalization or how our lives will be affected be it.The information technology revolution has undoubtedly facilitated such developments. It has brought great benefits, but arguably, it has also led to a greater sense of economic insecurity for some people and fueled anti-globalization sentiments in many activities, technology matters and technological capability has spread.Now-a-days women in India are getting freedom of working, freedom of having education and freedom from social superstitions.This happens only due to globalization. Indian women are contributing in national development by working in production sector of the economy.No sector is now being untouched from participation of women.But it is fact that Indian women are actively participating in agriculture sector and unorganized sector. Women are involved in the working of peasantry, dairy, fisheries and weaving industry.Their work is not recognized by the society.This is very disappointing situation.The Process of globalization needs to be placed in perspective. Trade liberalization and IT reinforce each other: Liberalization provides opportunity to producers to locate anywhere and yet retain access to their markets information networks provide easy means by which customers can purchase and producers can coordinate production and global scale. Women have got the opportunities of working in production of different industries.Exposure to domestic competition is an important part of the process.Productivity and growth may also-increase through exports.Some of the about globalization implies that the growth rates of our manufacturing industries are largely determined by their abilities to compete in the world.